Soft Skills formation in professional-oriented foreign language education at higher education institutions. - Buhinska, Tetiana; Hladkoskok, Lesia; Botvinko-Botiuk, Olena; Tytun, Oksana; Demianenko, Olena (Eduweb-Revista de Tecnologia de Informacion y Comunicacion en Educacion, 2022)
The article aims to analyze the constituent characteristics of soft skills and evaluate students' existing skills and their readiness to receive professionally-oriented foreign language training. General scientific methods of cognition are used for the study, including analysis of foreign investigations, periodicals, and surveys conducted by experts and scientists. During the study, the requirements of employers to the personnel for the qualities of soft skills in students are determined. The results show that in foreign language teaching, insufficient attention is paid to the education of these qualities. The study results are of great importance for the higher education teachers forming methodological developments in fostering these soft skills among students.
Keywords: soft skills, flexible skills, social skills, quality of higher education, competence, employability